Edukasi Dan Skrining Kesehatan Kulit Pada Kelompok Lanjut Usia - Sukmawati Tansil Tan; Alexander Halim Santoso; Triyana Sari; William Gilbert Satyanegara; Dean Ascha Wijaya; Bruce Edbert; Brian Albert Gaofman; Valentino Gilbert Lumintang (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Aging of the skin that occurs in the elderly has an impact on skin moisture. There are various factors that can influence skin moisture, both unchangeable and changeable. Disturbed skin moisture can cause various skin problems and reduce the sufferer's quality of life. This makes it important to provide education and skin hydration screening to the public, especially the elderly. Education is carried out by conveying information about skin moisture, influencing factors, as well as ways to prevent and care for the skin. The increasing number of elderly people in Indonesia makes it important for us to pay attention to their health. Skin care that can be done to maintain skin hydration includes using moisturizers, humidifiers in rooms with low humidity, using soft soap without fragrance, avoiding long showers, using sunscreen, and clothing that is not too tight. It is hoped that education and screening can increase public awareness regarding the importance of maintaining skin hydration, especially for the elderly, with the ultimate goal of improving the quality of public health in Indonesia.